Pengaruh Sikap Kemandirian, Motivasi, Kecerdasan Emosional, Pendidikan Kewirausahaan Terhadap Minat Berwirausaha (Studi Pada Wilayah Driyorejo Gresik) - Siti Djamilah; Widya Ributiati Utama (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2020)
Driyorejo is a district located in Gresik Regency, over time Driyorejo became a very crowded place due to the large number of housing developments and Driyorejo is an industrial area. This makes Driyorejo currently a very densely populated region. Increasing population makes people take advantage of these opportunities to meet their daily needs. Some people switch professions from farmers to trade or entrepreneurship. This study aims to examine the effect of attitude of independence, motivation, emotional intelligence, and entrepreneurship education on entrepreneurial interest. This study uses primary data obtained by distributing questionnaires to a number of respondents. The population in this study are entrepreneurs in the Driyorejo Gresik area. The sample used in this study was 100 respondents using purposive sampling technique. Data analysis method used is multiple linear regression analysis using the SPSS (Statistical Product and Service Solutions) program. The results of this study, it can be concluded that the variables of motivation, emotional intelligence and entrepreneurship education significantly influence the interests of entrepreneurship. However, the attitude of independence does not significantly influence the interest in entrepreneurship